Structural economic changes in China and Vietnam: Policy issues and consequences for agriculture. - Tisdell, C.A. (University of Queensland, 2011)
This paper outlines sectoral economic changes that have occurred in China and Vietnam following their market reforms and rapid economic growth. Bothe economies have experienced increased urbanization and a decline in the relative contribution of agriculture to GDP and to employment. There has been considerable movement of labor from agricultural to non-agricultural employment. Such movements are, however, not costless to farm families, particularly if migration is involved. The role of China‟s town-and-village enterprises in facilitating switching from agricultural to non-agricultural employment is discussed. Economic growth has resulted in considerable alterations in the composition of agriculture in China and Vietnam. A prominent trend is the expansion of livestock production relative to crop production. However, domestic livestock supplies have been outpaced by rising demand and in recent years their prices have risen. This has led some policy makers to argue that the heavy dependence of China and Vietnam on small-scale household producers of agricultural products is the main bottleneck. They favor policies to increase production by commercial enterprises. It is argued here that because both the economies of China and Vietnam are still in transition, it is economic to have agricultural products for which there is a high demand supplied by both households and commercial enterprises, even though this dual system is likely to disappear eventually.